Analis Faktor Penghambat Perkembangan Perbankan Syariah Di Kalimantan Timur - Mona hayati; Nirmala Agustina; Virda bin Jusman; Helda Indah Sari; Gesti Wulandari (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2022)
Along with the development of the Indonesian state, Islamic banking plays an important role in achieving the goal of building a just and prosperous society based on economic democracy based on the values of justice, unity, and benefit in line with sharia principles. The Islamic banking industry in East Kalimantan has a lot of potential, but there are still many obstacles in the way. The purpose of this study is to examine the barriers to the expansion of Islamic banking in the region. This research uses qualitative techniques with an emphasis on the literature approach method, which is a way to collect and evaluate data from various sources relevant to the research problem. The research also utilized relevant statistical data and conversations with relevant stakeholders. The conclusion of this study shows that although Islamic banking has made significant strides, a number of challenges remain to be resolved to enhance the resilience and growth of the industry. Lack of goods and services that cater to local needs, regulatory gaps between conventional and Islamic banking, and limited public awareness of the concept and advantages of Islamic banking are some of the main obstacles to Islamic banking in East Kalimantan. This research provides a significant addition to stakeholders' understanding of the dynamics and difficulties facing Islamic banking in the East Kalimantan region. This journal aims to examine the reasons behind the slow growth of Islamic banking in East Kalimantan.